Sensitive and non-invasive assessment of hepatocellular iron using a novel room-temperature susceptometer - Müller, Johannes; Raisi, Hanna; Rausch, Vanessa; Peccerella, Teresa; Simons, David; Ziener, Christian H.; Schlemmer, Heinz-Peter; Seitz, Helmut K.; Waldburger, Nina; Longerich, Thomas; Straub, Beate Katharina; Mueller, Sebastian (Journal of hepatology, 2017)
Background & Aims Liver iron accumulates in various chronic liver diseases where it is an independent factor for survival and carcinogenesis. We tested a novel room-temperature susceptometer (RTS) to non-invasively assess liver iron concentration (LIC). Methods Two hundred and sixty-four patients with or without signs of iron overload or liver disease were prospectively enrolled. Thirty-five patients underwent liver biopsy with semiquantitative iron determination (Prussian Blue staining), atomic absorption spectroscopy (AAS, n=33), or magnetic resonance imaging (MRI, n=15). Results In vitro studies demonstrated a highly linear (r2=0.998) association between RTS-signal and iron concentration, with a detection limit of 0.3mM. Using an optimized algorithm, accounting for the skin-to-liver capsule distance, valid measurements could be obtained in 84% of cases. LIC-RTS showed a significant correlation with LIC-AAS (r=0.74, p<0.001), LIC-MRI (r=0.64, p<0.001) and hepatocellular iron (r=0.58, p<0.01), but not with macrophage iron (r=0.32, p=0.30). Normal LIC-RTS was 1.4mg/g dry weight. Besides hereditary and transfusional iron overload, LIC-RTS was also significantly elevated in patients with alcoholic liver disease. The areas under the receiver operating characteristic curve (AUROC) for grade 1, 2 and 3 hepatocellular iron overload were 0.72, 0.89 and 0.97, respectively, with cut-off values of 2.0, 4.0 and 5.0mg/g dry weight. Notably, the positive and negative predictive values, sensitivity, specificity and accuracy of severe hepatic iron overload (HIO) (grade ≥2) detection, were equal to AAS and superior to all serum iron markers. Depletion of hepatic iron could be efficiently monitored upon phlebotomy. Conclusions RTS allows for the rapid and non-invasive measurement of LIC. In comparison to MRI, it could be a cost-effective bedside method for LIC screening. Lay summary: Novel room-temperature susceptometer (RTS) allows for the rapid, sensitive, and non-invasive measurement of liver iron concentration. In comparison to MRI, it could be a cost-effective bedside method for liver iron concentration screening.
Gesehen am 30.05.2018